Sometimes Ignorance is Bliss: Investigating Citizen Perceptions of the Certainty and Severity of Punishment - Piquero, Alex R. (American journal of criminal justice, 2012)
Deterrence lies at the heart of the criminal justice system and policy. There is a lack of information on citizen’s perceptions regarding a critical element of the deterrence process as it manifests through the communication of sanction threats. This study uses data from over 400 adults to examine their knowledge regarding the probability of detection and the average punishments for DUI, and also assesses the contribution of demographic and theoretical variables in predicting perceptions of detection probabilities and punishment estimates. Results show that persons over-estimate the likelihood of detection and provide higher estimates for average sentence lengths, but very few variables predict deterrence perceptions. An investigation of the resetting effect shows that persons tend to lower the estimated likelihood of punishment after experiencing a punishment. Deterrence may work better if researchers and policy officials understand what influences these perceptions and how they may be modified.